2013
DOI: 10.1177/0261927x13479188
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis of Expressive Writing Narratives About Stressful Relational Events Using Interpersonal Decentering

Abstract: This study used secondary analysis of data from two studies of expressive writing about stressful relational events to first describe the relations of word use to social-cognitive maturity of role-taking using Feffer’s Interpersonal Decentering scoring system and then to test hypotheses about active processing of relational information versus event closure. This scoring system for imaginative Thematic Apperception Test stories was adapted for expressive writing protocols and related to proportions of cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Clients’ psychological mindedness and insight into relational patterns are both important elements of psychodynamic psychotherapy and constructs of interest for interpersonal decentering. Jenkins and colleagues (2013) found that expressive writing essays that scored higher in interpersonal decentering contained more insight words. Might clients who engaged more mature interpersonal decentering processes be more likely to notice and recall psychodynamic interventions than cognitive-behavioral ones?…”
Section: Interpersonal Decenteringmentioning
confidence: 95%
See 2 more Smart Citations
“…Clients’ psychological mindedness and insight into relational patterns are both important elements of psychodynamic psychotherapy and constructs of interest for interpersonal decentering. Jenkins and colleagues (2013) found that expressive writing essays that scored higher in interpersonal decentering contained more insight words. Might clients who engaged more mature interpersonal decentering processes be more likely to notice and recall psychodynamic interventions than cognitive-behavioral ones?…”
Section: Interpersonal Decenteringmentioning
confidence: 95%
“…Feffer’s interpersonal decentering (Feffer, Leeper, Dobbs, Jenkins, & Perez, 2008; Leeper, Dobbs, & Jenkins, 2008) is a content analysis scoring system for thematic apperceptive techniques and other narrative tasks (Jenkins, Austin, & Boals, 2013; Jenkins et al, 2015). Mature decentering is conceptualized as the tendency to mobilize internalized reflective thoughts about people’s mental states when explaining their behavior (including one’s own); for example, when telling stories to explain the actions of people in a series of pictures (Jenkins et al, 2015).…”
Section: Interpersonal Decenteringmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of discourse analysis, the fictionality of a narrative has no bearing on its connection to real-life social cognition (Mar, 2018). Jenkins et al (2013) found that interpersonal decentering scored from EW essays was significantly related to cognitive, insight, and positive emotional word use in describing stressful interpersonal events. They suggested that decentering could provide a theory-based integrative contextual framework for understanding the previous fragmented LIWC findings.…”
Section: Studying the Narrator: Feffer's Interpersonal Decenteringmentioning
confidence: 99%
“…A few researchers have used more global ratings of narrative characteristics such as meaning making and narrative coherence (Klein & Boals, 2010). A more theory-grounded and empirically anchored approach, Feffer's interpersonal decentering scoring system (M. Feffer et al, 2008), measures interpersonal role-taking in narrative data (Jenkins et al, 2013). These three analysis systems appear to reflect more meaningful processing of stress response information than word-counting methods do.…”
mentioning
confidence: 99%